Future Directions in Oncology Research: Addressing Resistance and Improving Patient Outcomes - Mohammadi, Yasamin; Jalali, Fereshtehsadat; Sheikh, Madineh; Shakiba, Davoud; Mohammadiun Shabestari, Aida (Asian Pacific Journal of Cancer Nursing, 2025)
Background: Advances in oncology have substantially influenced the management strategies in cancer treatment, necessitating a comprehensive evaluation of contemporary practices alongside emerging technological breakthroughs. This review aims to encapsulate these advancements, with a focus on the integration of medical, and radiation oncology for a multidisciplinary treatment approach. Methods: Through systematic exploration of recent literature, this article examines pivotal developments in cancer management. Particular attention is given to the evolution and impact of targeted therapies and immunotherapies which have shifted traditional treatment paradigms and significantly improved patient outcomes. The review also delves into the burgeoning field of precision medicine and genomics, showcasing their role in tailoring personalized cancer therapies. Results: Our findings reveal that while the aforementioned innovations have led to more precise and effective treatment strategies, they also present substantial challenges, including resistance to therapies, issues with healthcare access, and the economic burden of new technologies. These aspects are critically analyzed to portray a realistic view of the advancements and hurdles within the current oncologic landscape. Conclusion: Looking forward, the article identifies key areas for future research that promise to further enhance the efficacy and accessibility of cancer treatments. By providing a detailed insight into the dynamic field of cancer treatment management, this review serves as a valuable resource for oncologists, researchers, and healthcare professionals, promoting informed decision-making and fostering innovation in the ongoing battle against cancer.